Pengaruh Senam Jantung Sehat terhadap Perubahan Tekanan Darah pada Penderita Hipertensi di Puskesmas Passo - Johanna Tomasoa; Abdul Rivai Saleh Dunggio (Syntax Corporation, 2023)
The formulation of the problem in this study is whether there is an effect of healthy heart gymnastics on changes in blood pressure in hypertensive patients in the working area of the Paso Health Center. Ambon, the purpose of the study was to determine the effect of heart-healthy healthy heart gymnastics on changes in blood pressure in hypertensive patients at the Passo Health Center. Ambon. The benefit of research is that it is an input for Puskesmas to be able to increase the knowledge of puskesmas officers and for people with hypertension to prevent stroke. The research method used in this study is Quasi-Experimental research, pseudo-Pre-Experiment, namely One Group Pretest Postest with control group. The population is hypertensive patients who seek treatment at the Paso Health Center. The sample was a hypertensive patient who went to the Paso Health Center. Data analysis techniques using paired t test. Hypothesis. Is there an effect of heart-healthy exercises, a healthy heart on changes in blood pressure in people with hypertension? The results of this study found that there was a significant difference in systole blood pressure before and after heart-healthy healthy heart exercise, the statistical test results of the significancy number were 0.000 with a mean difference of 15.33, and the confidence interval value (ik 95%) was between 9.554-21.113). And there was no significant difference in diastole blood pressure before and after heart-healthy exercises, the significancy figure was 0.187 with a mean difference of 2.667 and the confidence interval value (ik 95%) was between -1.369-6.702). Based on the paired sample t test, a value of p >0.05 was obtained